IMPLEMENTING PUBLIC EDUCATION TO IMPROVE BASIC LIFE SUPPORT FOR OUT-OF-HOSPITAL CARDIAC ARREST VICTIMS - Ardiansyah, Fakrul; Amandus, Hieronimus; Baedlawi, Azhari; Handayani, Vitria Wuri (Community Service Journal of Indonesia, 2024)
The incidence of out-of-hospital cardiac arrest worldwide is increasing every year, and Indonesia is one of the countries where the exact incidence of out-of-hospital cardiac arrest is not yet known. The main cause of cardiac arrest is cardiovascular disease. Deaths in Indonesia due to cardiovascular diseases amount to 7.4 million (42.3%), with 6.7 million (38.3%) caused by Coronary Heart Disease (CHD) and 6.7 million (38.3%) caused by stroke. The incidence rate of heart disease in West Kalimantan is 7.89%, with hypertension incidence in individuals over 18 years old at 8.16% and in Kubu Raya Regency at 5.51%. The incidence of stroke in West Kalimantan is 0.96%. This has led to an increasing incidence of out-of-hospital cardiac arrest. The purpose of this community service is to provide knowledge about basic life support for cardiac arrest victims at SMAN 1 Sungai Ambawang. Providing education about preparedness for the general public is very important for enhancing knowledge. the education impact test results indicated that the median knowledge score before delivery education is 47, whereas the median knowledge score after delivery education was 87. The average difference between the pre-test and post-test knowledge scores was 40.40. A the Wilcoxon test show that p = 0.001 (α<0.05), signifying a substantial effect of education on knowledge of basic life support for out-of-hospital cardiac arrest victims at SMAN 1 Sungai Ambawang. we can conclude that our understanding of basic life support for out-of-hospital cardiac arrest victims has improved.